2019
DOI: 10.3390/rs11060660
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the X- and C-Band Polarimetric SAR Data for Plastic-Mulched Farmland Classification

Abstract: We present a classification of plastic-mulched farmland (PMF) and other land cover types using full polarimetric RADARSAT-2 data and dual polarimetric (HH, VV) TerraSAR-X data, acquired from a test site in Hebei, China, where the main land covers include PMF, bare soil, winter wheat, urban areas and water. The main objectives were to evaluate the outcome of using high-resolution TerraSAR-X data for classifying PMF and other land covers and to compare classification accuracies based on different synthetic apert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…Based on assessment of the relative importance of all the features, it was demonstrated that the Shannon entropy extracted using the C–P polarization decomposition method made an important contribution to the accuracy of dryland crop mapping. This finding is also in accord with the results of previous research [ 9 ]. The backscattering coefficient in different polarization modes and the polarization decomposition parameters extracted using the C–P, F–D, and Yamaguchi decomposition methods have been used widely for land-cover and land-use classification.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Based on assessment of the relative importance of all the features, it was demonstrated that the Shannon entropy extracted using the C–P polarization decomposition method made an important contribution to the accuracy of dryland crop mapping. This finding is also in accord with the results of previous research [ 9 ]. The backscattering coefficient in different polarization modes and the polarization decomposition parameters extracted using the C–P, F–D, and Yamaguchi decomposition methods have been used widely for land-cover and land-use classification.…”
Section: Discussionsupporting
confidence: 94%
“…In addition to these features, we also used other backscattering intensity features, e.g., the main diagonal elements in the Coherency Matrix, and the polarization parameters extracted using the MCSM decomposition approach to enhance the accuracy of dryland crop classification. This novel combination of various features is markedly different from that of previous studies [ 9 , 20 , 29 , 35 ]. For optimization of the process, we used the RF algorithm to identify the most important features and the critical dates of imagery acquisition, the use of which was shown to both improve significantly the efficiency of crop classification and reduce the workload and costs associated with crop mapping.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…With few exceptions focused on PMF land cover extraction [31,42,66], SAR data has been practically not used as a data source for PCG mapping. However, with the very recent arrival of very high spatio-temporal resolution SAR data provided by the new generation of small satellites (e.g., ICEYE SAR (https://www.iceye.com/)), with X-band radar imaging available even at a 1 m ground sample distance resolution [67], it is likely that there will be a need to test its promising potential in RSAGPM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LANDSAT‐8 and SENTINEL‐2 multispectral data have been used in a number of studies published recently (Jimenez‐Lao et al, 2020). Synthetic aperture radar (SAR) data was also used in a number of studies for the classification of plastic‐mulched farmland areas (e.g., Hasituya & Chen, 2017; Liu et al, 2019). A summary of latest studies using remote sensing data for mapping and monitoring PCGs plastic‐mulched horticulture areas is given in Appendix 1.…”
Section: Remote Sensing For Pcg Mapping: Available Datasetsmentioning
confidence: 99%